PERCEPATAN PENANGGULANGAN PENGANGGURAN DI DESA MELALUI OPTIMALISASI AKSES PROGRAM KETENAGAKERJAAN - Ni Nyoman Reni Suasih; Made Kembar Sri Budhi; Ida Ayu Nyoman Sakara; Ni Putu Wiwin Setyari; Putu Ayu Pramitha Purwanti; Ni Luh Karmini; I Made Endra Kartika Yudha (Universitas Mataram, 2022)
The problem of unemployment (including rural unemployment) is one of the macroeconomic problems that hinders regional development because it will cause other social problems. The more limited employment opportunities, especially in rural areas, the higher the unemployment rate and urbanization among rural communities. The Provincial Government of Bali has provided services to UPTD BLK-IP. Previous research mentioned the need for disseminating employment information as an effort to accelerate the handling of rural unemployment. The purpose of this community service is to bring employment programs closer, both training programs and workforce distribution carried out by the UPTD BLK-IP of Bali Province. This service activity was carried out in Selat Village, Klungkung Regency, Bali Province, which was still experiencing rural workforce problems. The method of implementing the activity is through verbal socialization and socialization through leaflet media. Pre-test and post-test were also carried out as well as monitoring and evaluation after socialization. Verbal socialization was carried out by providing information on the main functions and services of the UPTD BLK-IP of Bali Province, training targets and policies (triple skilling), and vocational training. After delivering the material, a discussion was held, as well as pre-test and post-test as a form of evaluating the achievement of verbal socialization goals. The results of the post-test showed an increase in the information understanding of the participants in the socialization as well as their interest and willingness to disseminate the information obtained. Further socialization was carried out by means of leaflets that presented employment information in a concise, concise, attractive and accessible manner. Leaflets are distributed and also placed in public places or facilities that are easily accessible by the public. This activity has been able to provide information to the Selat Village community regarding employment programs, especially the UPTD BLK-IP of Bali Province training program.